Theoretical and Methodological Features of the Analysis of the Basic Concepts of the Modern Theory of National Security - A. B. Feonichev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article discusses the basic concepts of modern security theory: “danger”, “threat”, “challenge”, “risk” and “interest”. Based on the analysis of the content and correlation of these terms, the essence, nature and causes of threats to the national security of the Russian Federation are consider. The authors propose a revised definition of “threat to national security” as “a potential problem situation, which, without timely detection and resolution may lead to violation of stable operation or the destruction of the state”. Analysis of modern scientific literature on national security issues has shown that the term “call”, used in the meaning of “signal messages”, does not coincide with the original meaning of the term, understood as “challenge” — a problem C Based on this, the concepts of “threat” and “challenge” (understood as a problem situation) are synonymous. As a result, the authors concluded that there are two different conceptual approaches to security. Eurasian, which is characterize by the “threat — danger — damage” model, and Anglo-Saxon, which considers the mechanism of threat development through the “interest — control — lack of control — challenge — risk” model. In this case, interest and control are consider in relation to resources, territories, technologies, challenge as a problem situation that needs to be solved and risk as a possibility of lost profits.